Making Mommies: Law, Pre-Implantation Genetic Diagnosis, and the Complications of Pre-Motherhood - Mutcherson, Kimberly M. (Columbia Journal of Gender and Law, 2008)
“The major threats from coming advances in reproductive technology are not medical but political, social and philosophical.” Debate and concern about the ability to manipulate human life through the use of reproductive technologies is not new. As the use of technology slowly spreads, it becomes necessary to critically evaluate how calls to regulate this technology, by constraining access to or limiting particular uses of particular technologies, will impact long-standing conundrums about reproduction, parenting, and the law. To that end, this Article focuses on three topics: 1) the potential for legal regulation of pre- implantation genetic diagnosis, also known as PGD; 2) the relationship between such future regulation and the existing legal landscape attendant to parenting, procreation, and pregnancy; 3) and the specific consequences for women of legal incursion into PGD decision-making. PGD refers to a process of testing embryos prior to implantation in order to determine various genetic characteristics. Pre-implantation testing is frequently employed to determine whether the future child will have a particular disease or disability, but testing can also be used simply to determine sex.